Cumyl‐CBMICA: A new synthetic cannabinoid receptor agonist containing a cyclobutyl methyl side chain. Issue 1 (23rd October 2020) - Halter, Sebastian; Pulver, Benedikt; Wilde, Maurice; Haschimi, Belal; Westphal, Folker; Riedel, Jan; Pütz, Michael; Schönberger, Torsten; Stoll, Stefanie; Schäper, Jan; Auwärter, Volker
Abstract: Since the beginning of the phenomenon of new psychoactive substances (NPS), synthetic cannabinoid receptor agonists (SCRAs) have been the largest and most prevalent subclass of these drugs in Europe. Many countries implemented specific legislation scheduling classes of substances defined on the basis of their chemical structure to reduce supply. We describe the identification and analytical characterization within the EU project ADEBAR plus of 1‐(cyclobutylmethyl)‐ N ‐(2‐phenylpropan‐2‐yl)‐1 H ‐indole‐3‐carboxamide which resulted in the formal notification through the Early Warning System of the European Monitoring Centre for Drug and Drug Addiction (EMCDDA). This is the first identification of this new SCRA worldwide and the analytical data was distributed (inter‐)nationally right after identification in 2019. First, the substance was isolated from the herbal material using preparative high‐performance liquid chromatography (HPLC). Structure elucidation and analytical characterization were performed using gas chromatography–mass spectrometry (GC–MS), gas chromatography‐solid state infrared spectroscopy (GC‐sIR), liquid chromatography‐electrospray ionization‐quadrupole time of flight‐mass spectrometry (LC‐ESI‐qToF‐MS), Raman spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy. The new compound contains a cyclobutyl methyl group as a side chain and has not been described in any patent to our knowledge. Based on the semisystematic nomenclature of SCRAs, we propose Cumyl‐CBMICA as a short name for the compound. Abstract : Structure elucidation of a new SCRA emerged on the German drug market. Analyses were performed by GC–MS, GC‐sIR, LC‐ESI‐qToF‐MS, NMR, and Raman spectroscopy.